(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Among all the large vessel territory stroke, middle cerebral artery (MCA) territory stroke is the most common . Outcome depends on awareness and availability of specific treatment and proper conservative management after stroke. This prospective cohort study enrolled 49 clinically and radiologically diagnosed MCA territory stroke patients admitted in Neurology Department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2018 to December 2020. The aim was to see the prognosis of the middle cerebral artery territory (MCA) stroke patient who were treated conservatively. The Modified Rankin Scale (mRS) was used to measure the prognosis just after admission, after three months, six months, one year and two years; and the mean scores were 3.88 ± 0.88, 3.33 ± 1.24, 2.98 ± 1.42, 2.67 ± 1.60 & 2.23 ± 1.56 respectively. Among 49 patients, 9 patients died over the study period; one patient within one month after stroke, 3 patients within 3 months and 5 patients within six months. Though death rate was high in first three months, the survived patients improved significantly with conservative management in next two years of follow-up period. BSMMU J 2021; 14(3): 74-78